Polishing composition, polishing method, and method for manufacturing semiconductor substrate
By using negatively charged abrasive particles and water-soluble polymers in the grinding combination, and controlling the pH value and washing conditions during the grinding process, the problem of poor surface residue reduction effect when grinding silicon nitride at high speed is solved, and efficient residue removal and high-speed grinding are achieved.
Patent Information
- Application Number
- JP2023169586
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-15
- Filing Date
- 2023-09-29
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, when the silicon nitride is polished at high speed, the reduction effect of surface residues is not ideal.
A grinding combination of abrasive particles containing negative charge forged and water-soluble polymers ensures that the pH of the grinding combination is below 7.0 and is washed with alkaline after grinding to enhance charge on the silicon nitride surface, thereby increasing repulsion to residues.
It is achieved that the amount of surface residues is significantly reduced while maintaining a high grinding speed when grinding silicon nitride at high speed.
Smart Images

Figure 2025043222000001 
Figure 2025043222000002 
Figure 2025043222000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polishing composition, a polishing method, and a method for producing a semiconductor substrate. [Background technology]
[0002] In recent years, new microfabrication technologies have been developed to accompany the high integration and high performance of LSI (Large Scale Integration). Chemical mechanical polishing (CMP) is one of these technologies, and is frequently used in the LSI manufacturing process, especially in the multi-layer wiring formation process, for planarizing interlayer insulating films, forming metal plugs, and forming buried wiring (damascene wiring).
[0003] The CMP has been applied to each process in semiconductor manufacturing, and one aspect of the invention is the application to a gate formation process in transistor manufacturing. When manufacturing a transistor, materials such as metal, silicon, silicon oxide, polycrystalline silicon, and silicon nitride may be polished, and there is a demand for polishing each material at high speed in order to improve productivity. In order to meet such a demand, for example, Patent Document 1 discloses a polishing composition that contains colloidal silica (sulfonic acid group (anion) modified colloidal silica) with an organic acid fixed thereto as an abrasive grain and has a pH of 6 or less, for the purpose of providing a polishing composition capable of polishing a polishing target having poor chemical reactivity such as silicon nitride at high speed. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2012-040671 A Summary of the Invention [Problem to be solved by the invention]
[0005] According to the technique described in Patent Document 1, silicon nitride can be polished at a high polishing rate. However, the reduction of residues on the surface of silicon nitride is insufficient, and there is room for improvement in this regard.
[0006] Therefore, an object of the present invention is to provide a means capable of polishing silicon nitride at high speed and further reducing residues on the silicon nitride surface. [Means for solving the problem]
[0007] The present inventors have conducted intensive research in view of the above problems, and have found that the above problems can be solved by a polishing composition that contains abrasive grains and a water-soluble polymer containing a structural unit derived from an acrylic acid ester, has a pH of less than 7.0, and has a negative zeta potential of the abrasive grains in the polishing composition, thereby completing the present invention. Effect of the Invention
[0008] According to the present invention, a means can be provided that can polish silicon nitride at high speed and further reduce residue on the silicon nitride surface. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] According to one embodiment of the present invention, there is provided a polishing composition comprising an abrasive grain and a water-soluble polymer containing a structural unit derived from an acrylic acid ester, having a pH of less than 7.0, and having a negative zeta potential of the abrasive grain in the polishing composition. According to such a polishing composition of the present invention, the polishing rate of silicon nitride is high, and the residue on the surface of silicon nitride can be further reduced.
[0010] Although the details of why the polishing composition of the present invention provides the above-mentioned effects are unclear, it is believed that the mechanism is as follows. Note that the mechanism is based on speculation, and the technical scope of the present invention is not limited by the mechanism.
[0011] The abrasive grains according to the present invention have a negative zeta potential in the polishing composition, and therefore can polish silicon nitride quickly under acidic conditions. In addition, the water-soluble polymer containing a structural unit derived from an acrylic acid ester contained in the polishing composition does not ionize under acidic conditions. In addition, the polishing object after polishing is washed under alkaline conditions, and the absolute value of the zeta potential of silicon nitride, whose surface has a negative zeta potential under alkaline conditions, can be increased (the zeta potential can be further reduced). This strengthens the electrostatic repulsion between the silicon nitride surface and the residue (e.g., organic residue), and it is believed that the residue on the silicon nitride surface is reduced. Due to the above-mentioned mechanism of action, it is believed that the polishing composition of the present invention can polish silicon nitride at high speed and can further reduce the residue on the silicon nitride surface.
[0012] In this specification, residue refers to foreign matter that adheres to the surface of the polished object.The example of residue is not particularly limited, but can be, for example, organic residue, particle residue derived from abrasive grain contained in polishing composition, residue made of components other than particle residue and organic residue, mixture of particle residue and organic residue, and other residues.
[0013] In this specification, the organic residue refers to a component of the foreign matter adhering to the surface of the polished object, which is composed of organic matter such as organic low molecular weight compounds and polymeric compounds, organic salts, etc. Examples of the organic residue adhering to the polished object include pad waste generated from the pad used in the polishing step described below, or components derived from additives contained in the polishing composition used in the polishing step.
[0014] In addition, since the organic residue is significantly different from other residues in color and shape, whether the residue is an organic residue can be determined by visual inspection, for example, by observation with a scanning electron microscope (SEM). In addition, whether the residue is an organic residue can be determined by elemental analysis using an energy dispersive X-ray analyzer (EDX) attached to the SEM, as necessary. The number of organic residues can be measured using a wafer defect inspection device, or a wafer defect inspection device and SEM or EDX elemental analysis. Specifically, it can be measured by the method described in the examples.
[0015] The embodiments of the present invention will be described in detail below, but the present invention is not limited to the following embodiments and can be modified in various ways within the scope of the claims. The embodiments described in this specification can be combined in any way to form other embodiments. In this specification, unless otherwise specified, operations and measurements of physical properties are performed under conditions of room temperature (20°C to 25°C) and relative humidity of 40% RH to 50% RH.
[0016] [Abrasive grain] The polishing composition according to the present invention contains abrasive grains. The abrasive grains have the function of mechanically polishing an object to be polished, and increase the polishing rate of the object to be polished by the polishing composition.
[0017] In the polishing composition of the present invention, the abrasive grains have a negative zeta potential. Here, the "zeta (ζ) potential" refers to the potential difference that occurs at the interface between a solid and a liquid when they are in contact with each other and undergo relative motion. When the zeta potential of the abrasive grains is 0 mV or more (0 mV or positive), the polishing speed of silicon nitride decreases.
[0018] In the polishing composition of the present invention, the zeta potential of the abrasive grains is preferably from -60 mV to -10 mV, more preferably from -50 mV to -10 mV, and even more preferably from -45 mV to -15 mV. When the abrasive grains have a zeta potential in this range, the polishing speed of silicon nitride can be further improved.
[0019] Here, the zeta potential of the abrasive grains in the polishing composition is a value measured by the method described in the Examples. The zeta potential of the abrasive grains can be adjusted by the amount of anionic groups (particularly organic acid groups) contained in the abrasive grains described below, the pH of the polishing composition, etc.
[0020] The type of abrasive grain is not particularly limited, and examples thereof include metal oxides such as silica, alumina, zirconia, and titania. The abrasive grain may be used alone or in combination of two or more kinds. The abrasive grain may be a commercially available product or a synthetic product.
[0021] The type of abrasive grain is preferably silica, more preferably colloidal silica.The method for producing colloidal silica includes sodium silicate method and sol-gel method, and the colloidal silica produced by any method can be suitably used as the abrasive grain of the present invention.However, from the viewpoint of reducing metal impurities, the colloidal silica produced by the sol-gel method is preferred because it can be produced with high purity.
[0022] Colloidal silica can be produced by the sol-gel method using a conventionally known method. Specifically, colloidal silica can be obtained by using a hydrolyzable silicon compound (e.g., alkoxysilane or a derivative thereof) as a raw material and carrying out a hydrolysis-condensation reaction.
[0023] In some embodiments of the present invention, the colloidal silica contained in the polishing composition is preferably anion-modified colloidal silica (anion-modified colloidal silica), more preferably colloidal silica with organic acid fixed on the surface. Colloidal silica with organic acid fixed on the surface tends to have a larger absolute value of zeta potential in the polishing composition than normal colloidal silica with no organic acid fixed on the surface. Therefore, the zeta potential of colloidal silica in the polishing composition is easily adjusted to be negative.
[0024] Preferred examples of colloidal silica having an organic acid fixed to its surface include colloidal silica having an organic acid group, such as a carboxylic acid group, a sulfonic acid group, a phosphonic acid group, or an aluminic acid group, fixed to its surface. Among these, colloidal silica having a sulfonic acid or a carboxylic acid fixed to its surface is preferred from the viewpoint of ease of production, and colloidal silica having a sulfonic acid fixed to its surface (sulfonic acid fixed colloidal silica, sulfonic acid modified colloidal silica, sulfonic acid modified colloidal silica) is more preferred.
[0025] The immobilization of an organic acid on the surface of colloidal silica cannot be achieved by simply allowing colloidal silica and an organic acid to coexist. For example, if sulfonic acid, which is a type of organic acid, is to be immobilized on colloidal silica, it can be achieved by the method described in, for example, “Sulfonic acid-functionalized silica through quantitative oxidation of thiol groups”, Chem. Commun. 246-247 (2003). Specifically, a silane coupling agent having a thiol group, such as 3-mercaptopropyltrimethoxysilane, is coupled to colloidal silica, and then the thiol group is oxidized with hydrogen peroxide to obtain colloidal silica with sulfonic acid immobilized on the surface (sulfonic acid immobilized colloidal silica, sulfonic acid modified colloidal silica).
[0026] Alternatively, when a carboxylic acid, which is a type of organic acid, is immobilized on colloidal silica, it can be carried out by, for example, the method described in “Novel Silane Coupling Agents Containing a Photolabile 2-Nitrobenzyl Ester for Introduction of a Carboxy Group on the Surface of Silica Gel”, Chemistry Letters, 3, 228-229 (2000). Specifically, a silane coupling agent containing a photoreactive 2-nitrobenzyl ester is coupled to colloidal silica, followed by light irradiation, to obtain colloidal silica with a carboxylic acid immobilized on the surface (carboxylic acid-modified colloidal silica, carboxylic acid-modified colloidal silica).
[0027] The shape of the abrasive grains is not particularly limited, and may be spherical or non-spherical. Specific examples of non-spherical shapes include polygonal prisms such as triangular prisms and square prisms, cylinders, bales in which the center of a cylinder is bulged out more than the ends, donut shapes in which the center of a disk is penetrated, plates, so-called cocoon shapes with a constriction in the center, so-called association-type spheres in which multiple particles are integrated, so-called confetti shapes with multiple protrusions on the surface, and rugby ball shapes, and various other shapes are not particularly limited.
[0028] The size of the abrasive grains is not particularly limited. For example, the average primary particle diameter of the abrasive grains is preferably 5 nm or more, more preferably 8 nm or more, even more preferably 10 nm or more, and particularly preferably 12 nm or more. As the average primary particle diameter of the abrasive grains increases, the polishing speed of the object to be polished by the polishing composition increases. In addition, the average primary particle diameter of the abrasive grains is preferably 100 nm or less, more preferably 80 nm or less, and even more preferably 50 nm or less. As the average primary particle diameter of the abrasive grains decreases, it becomes easier to obtain a surface with fewer defects by polishing with the polishing composition. That is, the average primary particle diameter of the abrasive grains is preferably 5 nm or more and 100 nm or less, more preferably 8 nm or more and 80 nm or less, even more preferably 10 nm or more and 50 nm or less, and particularly preferably 12 nm or more and 50 nm or less. The average primary particle diameter of the abrasive grains can be calculated, for example, based on the specific surface area (SA) of the abrasive grains calculated by the BET method, assuming that the shape of the abrasive grains is a true sphere. In this specification, the average primary particle size of the abrasive grains is a value measured by the method described in the Examples.
[0029] In addition, the average secondary particle diameter of the abrasive grains is preferably 10 nm or more, more preferably 15 nm or more, even more preferably 20 nm or more, and particularly preferably 25 nm or more. As the average secondary particle diameter of the abrasive grains increases, the resistance during polishing decreases, and stable polishing becomes possible. In addition, the average secondary particle diameter of the abrasive grains is preferably 400 nm or less, more preferably 300 nm or less, even more preferably 200 nm or less, particularly preferably 100 nm or less, and most preferably 80 nm or less. As the average secondary particle diameter of the abrasive grains decreases, the surface area per unit mass of the abrasive grains increases, the contact frequency with the object to be polished increases, and the polishing speed increases. That is, the average secondary particle diameter of the abrasive grains is preferably 10 nm or more and 400 nm or less, more preferably 15 nm or more and 300 nm or less, even more preferably 20 nm or more and 200 nm or less, even more preferably 25 nm or more and 100 nm or less, and particularly preferably 25 nm or more and 80 nm or less. The average secondary particle size of the abrasive grains can be measured by, for example, a dynamic light scattering method such as a laser diffraction scattering method.
[0030] The average degree of association of the abrasive grains is preferably 5.0 or less, more preferably 4.0 or less, even more preferably 3.0 or less, and particularly preferably 2.5 or less. As the average degree of association of the abrasive grains decreases, defects can be reduced more. The average degree of association of the abrasive grains is also preferably 1.0 or more, more preferably 1.5 or more, and even more preferably 2.0 or more. This average degree of association is obtained by dividing the value of the average secondary particle diameter of the abrasive grains by the value of the average primary particle diameter. As the average degree of association of the abrasive grains increases, there is an advantageous effect that the polishing speed of the object to be polished by the polishing composition improves.
[0031] The upper limit of the aspect ratio of the abrasive grains in the polishing composition is not particularly limited, but is preferably less than 2.0, more preferably 1.8 or less, and even more preferably 1.5 or less. In such a range, defects on the surface of the object to be polished can be further reduced. The aspect ratio is the average of the values obtained by taking the smallest rectangle that circumscribes the image of the abrasive grains by a scanning electron microscope, and dividing the length of the long side of the rectangle by the length of the short side of the same rectangle, and can be determined using general image analysis software. The lower limit of the aspect ratio of the abrasive grains in the polishing composition is not particularly limited, but is preferably 1.0 or more, and more preferably 1.2 or more.
[0032] In the particle size distribution of abrasive grains obtained by laser diffraction scattering method, the lower limit of D90 / D10, which is the ratio of the particle diameter (D90) when the cumulative particle mass from the fine particle side reaches 90% of the total particle mass and the particle diameter (D10) when the cumulative particle mass from the fine particle side reaches 10% of the total particle mass of all particles, is not particularly limited, but is preferably 1.1 or more, more preferably 1.4 or more, even more preferably 1.7 or more, and most preferably 2.0 or more. In addition, in the particle size distribution of abrasive grains in a polishing composition obtained by laser diffraction scattering method, the upper limit of the ratio D90 / D10, which is the particle diameter (D90) when the cumulative particle mass from the fine particle side reaches 90% of the total particle mass and the particle diameter (D10) when the cumulative particle mass from the fine particle side reaches 10% of the total particle mass of all particles, is not particularly limited, but is preferably 3.0 or less, more preferably 2.5 or less. Within such a range, defects on the surface of the object to be polished can be further reduced.
[0033] The size of the abrasive grains (average primary particle size, average secondary particle size, aspect ratio, D90 / D10, etc.) can be appropriately controlled by selecting the manufacturing method of the abrasive grains, etc.
[0034] The concentration (content) of the abrasive grains is not particularly limited, but is preferably 0.5% by mass or more, more preferably 0.8% by mass or more, even more preferably 1% by mass or more, even more preferably more than 1% by mass, and particularly preferably 1.5% by mass or more, based on the total mass of the polishing composition. The concentration (content) of the abrasive grains is preferably 20% by mass or less, more preferably 15% by mass or less, even more preferably 10% by mass or less, and particularly preferably 5% by mass or less, based on the total mass of the polishing composition. That is, the concentration (content) of the abrasive grains is preferably 0.5% by mass or more and 20% by mass or less, more preferably 0.8% by mass or more and 20% by mass or less, even more preferably 1% by mass or more and 15% by mass or less, even more preferably more than 1% by mass and 10% by mass or less, and particularly preferably 1.5% by mass or more and 5% by mass or less, based on the total mass of the polishing composition. Within such a range, the polishing speed can be improved while suppressing costs. When the polishing composition contains two or more types of abrasive grains, the concentration (content) of the abrasive grains means the total amount of these.
[0035] [Water-soluble polymers containing structural units derived from acrylate esters] The polishing composition according to the present invention contains a water-soluble polymer containing a structural unit derived from an acrylic acid ester. The water-soluble polymer does not ionize under acidic conditions. In addition, the polishing object after polishing is washed under alkaline conditions, and the absolute value of the zeta potential of silicon nitride, whose surface has a negative zeta potential under alkaline conditions, can be increased (the zeta potential can be reduced). This strengthens the electrostatic repulsion between the silicon nitride surface and the residue (e.g., organic residue), and reduces the residue on the silicon nitride surface.
[0036] The water-soluble polymer containing a structural unit derived from an acrylic acid ester will be described below. In the following description, for convenience, the water-soluble polymer will also be referred to as "water-soluble polymer A."
[0037] In this specification, "water-soluble" means that the solubility in water (25°C) is 1 g / 100 mL or more, and "polymer" means a (co)polymer having a weight average molecular weight (Mw) of 200 or more. The weight average molecular weight (Mw) may be a catalog value, or it can be measured by gel permeation chromatography (GPC). When it is not possible to measure by GPC, the molecular weight calculated from the molecular formula can be used as the weight average molecular weight of the water-soluble polymer.
[0038] Examples of the acrylic acid esters include methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-pentyl acrylate, neopentyl acrylate, cyclopentyl acrylate, n-hexyl acrylate, isohexyl acrylate, cyclohexyl acrylate, n-heptyl acrylate, n-octyl acrylate, 2-ethylhexyl acrylate, n-nonyl acrylate, n-decyl acrylate, n-dodecyl acrylate, n-tridecyl acrylate, n-tetradecyl acrylate, n-pentadecyl acrylate, n-hexadecyl acrylate, a Examples of the acrylic acid alkyl ester include those having a linear, branched, or cyclic alkyl group having 1 to 20 carbon atoms, such as n-heptadecyl acrylate, n-octadecyl acrylate, and isobornyl acrylate; those containing functional groups, such as 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 3-hydroxypropyl acrylate, 2-hydroxybutyl acrylate, 4-hydroxybutyl acrylate, 6-hydroxyhexyl acrylate, 2-methoxyethyl acrylate, glycidyl acrylate, trimethylsilyl acrylate, and 2-(N,N-dimethylamino)ethyl acrylate; and those containing aromatic groups, such as phenyl acrylate and benzyl acrylate. These acrylic acid esters can be used alone or in combination of two or more. When two or more acrylic acid esters are used, the water-soluble polymer A becomes a copolymer, but the form is not particularly limited, and may be any of block copolymers, random copolymers, alternating copolymers, and graft copolymers.
[0039] Among these acrylic esters, at least one selected from the group consisting of methyl acrylate, ethyl acrylate, butyl acrylate, and 2-ethylhexyl acrylate is preferred.
[0040] From the viewpoint of further improving the effects of the present invention, it is more preferable that the water-soluble polymer A further contains a structural unit derived from another monomer (hereinafter, also simply referred to as "other monomer") that is copolymerizable with the above-mentioned acrylic acid ester. When the water-soluble polymer A contains a structural unit derived from another monomer, the water-soluble polymer A becomes a copolymer, but the form thereof is not particularly limited, and may be any of a block copolymer, a random copolymer, an alternating copolymer, a graft copolymer, etc.
[0041] Examples of such other monomers include α-olefin compounds such as ethylene, propylene, 1-butene, 1-pentene, 3-methyl-1-butene, and 1-hexene; vinyl esters such as vinyl acetate, vinyl propionate, vinyl pivalate, vinyl caprate, and vinyl benzoate; unsaturated carboxylic acids or salts thereof such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, fumaric acid, and itaconic acid; unsaturated carboxylic anhydrides such as maleic anhydride; (meth)acrylamide, N-methylmethacrylamide, N-ethylmethacrylamide, N-isopropylmethacrylamide, N,N-dimethylmethacrylamide, N,N-diethylmethacrylamide, acrylamide, N-methylacrylamide, N-ethylacrylamide, N-isopropylacrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, and (meth)acrylic acid N-methylolamide. Examples of the monomers include acrylamide, N-vinylpyrrolidone, (meth)acrylonitrile such as acrylonitrile and methacrylonitrile, vinyl aromatic compounds such as styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, and p-styrenesulfonic acid or salts thereof, conjugated diene compounds such as butadiene, isoprene, and 1,3-pentadiene, maleimide compounds such as N-methylmaleimide, N-phenylmaleimide, and N-cyclohexylmaleimide, vinylsilane compounds such as vinyltrimethoxysilane, vinylmethyldimethoxysilane, and vinyldimethylmethoxysilane, N-vinylcarbazole, alkyl vinyl ether compounds such as methyl vinyl ether, and α-olefin compounds containing functional groups such as hydroxyl groups, such as 3-methyl-3-buten-1-ol, 3-buten-1-ol, methallyl alcohol, allyl alcohol, and octa-2,7-dienyl alcohol. These other monomers may be used alone or in combination of two or more.
[0042] Among these other monomers, unsaturated carboxylic acids or their salts are preferred from the viewpoint of more easily exerting the effects of the present invention. Examples of the salts include alkali metal salts (lithium salts, sodium salts, potassium salts, etc.), alkaline earth metal salts (magnesium salts, calcium salts, barium salts, etc.), aluminum salts, ammonium salts, and organic amine salts. The other monomer is more preferably an ammonium salt of an unsaturated carboxylic acid, and even more preferably ammonium acrylate.
[0043] When the water-soluble polymer A contains structural units derived from other monomers, the mass ratio of the structural units derived from acrylic acid esters to the structural units derived from other monomers in the water-soluble polymer A (structural units derived from acrylic acid esters:structural units derived from other monomers) is preferably 10:90 to 90:10, and more preferably 20:80 to 80:20.
[0044] More specific examples of the water-soluble polymer A include, for example, methyl acrylate-ammonium acrylate copolymer, ethyl acrylate-ammonium acrylate copolymer, propyl acrylate-ammonium acrylate copolymer, butyl acrylate-ammonium acrylate copolymer, and the like.
[0045] The water-soluble polymer A may be used alone or in combination of two or more. The water-soluble polymer A may be a commercially available product or a synthetic product. An example of a commercially available water-soluble polymer A is Aron (registered trademark) A-6114 (manufactured by Toagosei Co., Ltd.).
[0046] The weight average molecular weight of the water-soluble polymer A is not particularly limited, but is preferably 1,000 or more, preferably 3,000 or more, and more preferably 5,000 or more. The weight average molecular weight of the water-soluble polymer A is not particularly limited, but is preferably 100,000 or less, more preferably 80,000 or less, and even more preferably 50,000 or less. That is, the weight average molecular weight of the water-soluble polymer A is preferably 1,000 or more and 100,000 or less, preferably 3,000 or more and 80,000 or less, and even more preferably 5,000 or more and 50,000 or less.
[0047] The concentration (content) of the water-soluble polymer A is not particularly limited, but is preferably 0.005% by mass or more, more preferably 0.01% by mass or more, and even more preferably 0.02% by mass or more, based on the total mass of the polishing composition. The concentration (content) of the water-soluble polymer A is preferably 1.0% by mass or less, more preferably 0.5% by mass or less, and even more preferably 0.1% by mass or less, based on the total mass of the polishing composition. That is, the concentration (content) of the water-soluble polymer A is preferably 0.005% by mass or more and 1.0% by mass or less, more preferably 0.01% by mass or more and 0.5% by mass or less, and even more preferably 0.02% by mass or more and 0.1% by mass or less, based on the total mass of the polishing composition. If it is within such a range, the effect of the present invention is further improved. In addition, when the polishing composition contains two or more kinds of water-soluble polymers A, the concentration (content) of the water-soluble polymer A means the total amount of these.
[0048] [Inorganic salts] The polishing composition of the present invention preferably further contains an inorganic salt. It is believed that the inclusion of an inorganic salt further reduces residues on the silicon nitride surface.
[0049] Examples of inorganic salts include inorganic salts composed of the following cations and anions. Examples of cations include alkali metal ions such as lithium ion, sodium ion, and potassium ion, alkaline earth metal ions such as magnesium ion, calcium ion, and strontium ion, polyatomic ions such as ammonium ion, and complex ions. Examples of anions include halide ions (fluoride ion, chloride ion, bromide ion, iodide ion, etc.), oxoacid ions (borate ion, carbonate ion, nitrate ion, nitrite ion, metasilicate ion, phosphate ion, monohydrogen phosphate ion, dihydrogen phosphate ion, phosphonate ion, monohydrogen phosphonate ion, phosphinate ion, sulfate ion, sulfonate ion, sulfite ion, thiosulfate ion, chromate ion, dichromate ion, permanganate ion, etc.), thiocyanate ion, cyanate ion, and sulfamate ion.
[0050] More specific examples of inorganic salts consisting of inorganic cations and inorganic anions include lithium salts such as lithium chloride, lithium bromide, lithium carbonate, lithium nitrate, and lithium thiocyanate; calcium salts such as calcium chloride, calcium bromide, calcium carbonate, calcium nitrate, and calcium thiocyanate; iron salts such as iron nitrate and iron thiocyanate; potassium salts such as potassium chloride, potassium bromide, potassium nitrate, potassium sulfate, potassium thiocyanate, potassium sulfamate, potassium phosphate, potassium dihydrogen phosphate, potassium monohydrogen phosphate, and potassium monohydrogen phosphonate; sodium salts such as sodium chloride, sodium bromide, sodium nitrate, sodium sulfate, and sodium thiocyanate; zinc salts such as zinc chloride, zinc nitrate, and zinc thiocyanate; magnesium salts such as magnesium nitrate, magnesium sulfate, and magnesium thiocyanate; strontium salts such as strontium nitrate and strontium thiocyanate; ammonium chloride, ammonium bromide, ammonium iodide, ammonium nitrate, ammonium phosphate, ammonium dihydrogen phosphate, ammonium monohydrogen phosphate, ammonium phosphonate, ammonium monohydrogen phosphonate, ammonium sulfate, ammonium thiocyanate, and ammonium sulfamate. These inorganic salts may be used alone or in combination of two or more. In addition, the inorganic salts to be used may be commercially available products or synthetic products.
[0051] Among these, from the viewpoint of more effectively exerting the effects of the present invention, inorganic salts in which the cation is a potassium ion or an ammonium ion and the anion is an oxoacid ion or a thiocyanate ion are preferred.Furthermore, the inorganic salt is more preferably at least one selected from the group consisting of ammonium sulfate, potassium sulfate, ammonium nitrate, potassium nitrate, ammonium thiocyanate, potassium thiocyanate, potassium sulfamate, ammonium phosphate, ammonium phosphonate, ammonium sulfamate, ammonium dihydrogen phosphate, ammonium monohydrogen phosphate, potassium phosphate, potassium dihydrogen phosphate, potassium monohydrogen phosphate, ammonium monohydrogen phosphonate, potassium phosphonate, and potassium monohydrogen phosphonate, and more preferably ammonium sulfate.
[0052] The concentration (content) of inorganic salt in the polishing composition is not particularly limited, but in the case of the polishing composition that is used as it is as a polishing liquid for polishing the object to be polished, the lower limit of the concentration (content) of inorganic salt in the polishing composition is preferably 0.1 mass% or more, more preferably 0.2 mass% or more, and even more preferably 0.3 mass% or more, based on the total mass of the polishing composition.In addition, the upper limit of the concentration (content) of inorganic salt in the polishing composition is preferably 3.0 mass% or less, more preferably 2.5 mass% or less, and even more preferably 2.0 mass% or less, based on the total mass of the polishing composition.
[0053] That is, the concentration (content) of the inorganic salt is preferably 0.1 mass% or more and 3.0 mass% or less, more preferably 0.2 mass% or more and 2.5 mass% or less, and even more preferably 0.3 mass% or more and 2.0 mass% or less, relative to the total mass of the polishing composition.
[0054] When the polishing composition contains two or more kinds of inorganic salts, the concentration (content) of the inorganic salts means the total amount thereof.
[0055] [Water-soluble polymer B and water-soluble polymer C] The polishing composition according to the present invention may further contain a water-soluble polymer other than the water-soluble polymer A. The water-soluble polymer other than the water-soluble polymer A is not particularly limited, and any of a nonionic water-soluble polymer, an anionic water-soluble polymer, a cationic water-soluble polymer, and an amphoteric water-soluble polymer can be used. The water-soluble polymer other than the water-soluble polymer A may be used alone or in combination of two or more kinds. In addition, the water-soluble polymer may be a commercially available product or a synthetic product.
[0056] From the viewpoint of further improving the effect of the present invention, the polishing composition of the present invention preferably contains a water-soluble polymer that adsorbs to the surface of the object to be polished (particularly polysilicon) and changes the wettability of the surface from hydrophobic to hydrophilic. Such a water-soluble polymer can prevent redeposition of residues on the surface of the object to be polished after polishing.
[0057] In addition, the polishing composition according to the present invention preferably contains a water-soluble polymer having an effect of suppressing the polishing rate of the object to be polished (particularly polysilicon). Such a water-soluble polymer can be adsorbed on the surface of the object to be polished (particularly polysilicon) to form a protective film, and has the effect of inhibiting the mechanical polishing action of colloidal silica.
[0058] In the following, water-soluble polymers other than the water-soluble polymer A will be described. In the following description, for convenience, a water-soluble polymer that adsorbs to the surface of an object to be polished (particularly polysilicon) and has the effect of changing the wettability of the surface from hydrophobic to hydrophilic will also be referred to as "water-soluble polymer B", and a water-soluble polymer that has the effect of suppressing the polishing rate of an object to be polished (particularly polysilicon) will also be referred to as "water-soluble polymer C". The water-soluble polymers B and C shown below do not have a structural unit derived from an acrylic acid ester. That is, in this specification, all water-soluble polymers that contain a structural unit derived from an acrylic acid ester are classified as the water-soluble polymer A described above.
[0059] <Water-soluble polymer B> The water-soluble polymer B that can be included in the polishing composition according to the present invention has the effect of adsorbing to the surface of the object to be polished (particularly polysilicon) and changing the wettability of the surface of the object to be polished (particularly polysilicon) from hydrophobic to hydrophilic. The water-soluble polymer B used in the present invention is not particularly limited as long as it has the above-mentioned effect, but it can be one having at least one functional group selected from the group consisting of a nonionic group, an anionic group, and a cationic group in the molecule. Examples of the water-soluble polymer include those containing an alcoholic hydroxyl group, a carboxyl group, an acyloxy group, a sulfo group, a quaternary ammonium structure, a heterocyclic structure, and a vinyl structure in the molecule. From the viewpoint of more easily obtaining the effect of the present application, it is preferable that the water-soluble polymer B is a water-soluble polymer having an alcoholic hydroxyl group in the side chain.
[0060] The water-soluble polymer having an alcoholic hydroxyl group in the side chain is not particularly limited as long as it has such a structure, but a compound containing a vinyl alcohol unit (a structural portion represented by -CH2-CH(OH)-; hereinafter also referred to as "VA unit") in the structure is preferred.
[0061] The compound containing a VA unit in its structure may have all repeating units substantially composed of VA units. The compound containing a VA unit in its structure may further contain a non-vinyl alcohol unit (a structural unit derived from a monomer other than vinyl alcohol, hereinafter also referred to as a "non-VA unit") in addition to the VA unit. The non-VA unit is not particularly limited, and examples thereof include structural units derived from ethylene, vinyl acetate, vinyl propionate, vinyl hexanoate, 2-butenediol, etc. When a polymer containing a structural unit derived from vinyl alcohol contains a non-VA unit, it may contain only one type of non-VA unit, or may contain two or more types of non-VA units. In the compound containing a VA unit in its structure, the ratio of the number of moles of the VA unit to the number of moles of all repeating units is not particularly limited, but is preferably 50% or more, more preferably 65% or more, even more preferably 70% or more, and particularly preferably 75% or more (upper limit 100%).
[0062] The water-soluble polymer having an alcoholic hydroxyl group in its side chain is preferably at least one selected from the group consisting of polyvinyl alcohol, polyvinyl alcohol derivatives (polyvinyl alcohol derivatives having an alcoholic hydroxyl group in its side chain), copolymers of vinyl alcohol and other monomers (copolymers of vinyl alcohol and other monomers having an alcoholic hydroxyl group in its side chain), and derivatives of said copolymers (derivatives of copolymers of vinyl alcohol having an alcoholic hydroxyl group in its side chain and other monomers).
[0063] The degree of saponification of polyvinyl alcohol is not particularly limited, but is preferably 50 mol % or more, more preferably 65 mol % or more, even more preferably 70 mol % or more, and particularly preferably 75 mol % or more (upper limit 100 mol %).
[0064] An example of a polyvinyl alcohol derivative is modified polyvinyl alcohol, etc. Modified polyvinyl alcohol contains a structure in which a part of the alcoholic hydroxyl group of the vinyl alcohol unit is substituted with another functional group as a non-VA unit (hereinafter, also referred to as a "modified VA unit").
[0065] The modified polyvinyl alcohol is not particularly limited, but examples thereof include carboxy-modified polyvinyl alcohol, sulfonic acid-modified polyvinyl alcohol, phosphoric acid-modified polyvinyl alcohol, silanol-modified polyvinyl alcohol, epoxy-modified polyvinyl alcohol, acetoacetyl-modified polyvinyl alcohol, nitrile-modified polyvinyl alcohol, pyrrolidone-modified polyvinyl alcohol, silicone-modified polyvinyl alcohol, amino-modified polyvinyl alcohol, quaternary amino-modified polyvinyl alcohol, etc. In addition, the modified polyvinyl alcohol is not particularly limited, but examples thereof include compounds obtained by cyclic acetalization of polyvinyl alcohol (e.g., polyvinyl butyral, polyvinyl propylal, polyvinyl ethylal, polyvinyl methylal, etc.).
[0066] The derivatives of copolymers of vinyl alcohol and other monomers are not particularly limited, and examples thereof include compounds that further contain, in addition to VA units and modified VA units, structural units such as structural units derived from ethylene, structural units derived from vinyl ethers having a long-chain alkyl group, and structural units derived from compounds having at least one of an acryloyl group and a methacryloyl group.
[0067] Polysaccharides are also preferably used as the water-soluble polymer having an alcoholic hydroxyl group in the side chain. Examples of polysaccharides include dextrin, maltodextrin, isomaltodextrin (branched maltodextrin), cyclodextrin, branched cyclodextrin, roasted dextrin, polymeric dextrin, indigestible dextrin, inulin, inulin hydrolyzate, agave inulin, LM pectin, HM pectin, pullulan, guar gum, guar gum hydrolyzate, xanthan gum, gum arabic, gum ghatti, native gellan gum, deacylated gellan gum, locust bean gum, tara gum, galactomannan, glucomannan, konjac mannan, curdlan, karage, etc. Examples of suitable sugars include cellulose gum, maltose, maltose, maltitol, maltitol esters ...
[0068] Among these, the water-soluble polymer B is more preferably at least one of polyvinyl alcohol and a vinyl alcohol-butenediol copolymer, and further preferably polyvinyl alcohol.
[0069] The weight average molecular weight of the water-soluble polymer B is not particularly limited, but is preferably 1,000 or more, preferably 3,000 or more, and more preferably 5,000 or more. The weight average molecular weight of the water-soluble polymer B is not particularly limited, but is preferably 1,000,000 or less, more preferably 100,000 or less, and even more preferably 50,000 or less. That is, the weight average molecular weight of the water-soluble polymer B is preferably 1,000 or more and 1,000,000 or less, preferably 3,000 or more and 100,000 or less, and even more preferably 5,000 or more and 50,000 or less.
[0070] The water-soluble polymer B may be used alone or in combination of two or more. In addition, the water-soluble polymer B may be a commercially available product or a synthetic product.
[0071] The lower limit of the concentration (content) of the water-soluble polymer B in the polishing composition is preferably 0.005% by mass or more, more preferably 0.01% by mass or more, even more preferably 0.015% by mass or more, and particularly preferably 0.02% by mass or more, from the viewpoint of further increasing the hydrophilicity of the polishing object. The upper limit of the concentration (content) of the water-soluble polymer B in the polishing composition is preferably 1% by mass or less, more preferably 0.8% by mass or less, even more preferably 0.5% by mass or less, and particularly preferably 0.3% by mass or less. That is, the concentration (content) of the water-soluble polymer B in the polishing composition is preferably 0.005% by mass or more and 1% by mass or less, more preferably 0.01% by mass or more and 0.8% by mass or less, even more preferably 0.015% by mass or more and 0.5% by mass or less, and particularly preferably 0.02% by mass or more and 0.3% by mass or less.
[0072] When the polishing composition contains two or more kinds of water-soluble polymer B, the concentration (content) of the water-soluble polymer B means the total amount thereof.
[0073] <Water-soluble polymer C> The water-soluble polymer C used in the present invention is not particularly limited as long as it has the above-mentioned effect, but may be a nonionic compound or an anionic compound, and among them, a water-soluble polymer having a polyoxyalkylene chain is preferable. In addition, the water-soluble polymer C is preferably a nonionic compound from the viewpoint of preventing electrostatic adsorption to materials other than the material (particularly polysilicon) that suppresses the polishing rate.
[0074] In addition, a water-soluble polymer having an alcoholic hydroxyl group in a side chain and a polyoxyalkylene chain is classified as a water-soluble polymer C.
[0075] Examples of the water-soluble polymer C include polyethylene glycol (PEG), polypropylene glycol (PPG), polytetramethylene glycol, polytetramethylene ether glycol, polypentylene glycol, polyhexylene glycol, polyheptylene glycol, polyoctylene glycol, polynonylene glycol, polydecylene glycol, polyoxyethylene nonylphenyl ether (POE nonylphenyl ether); at least two kinds of block copolymers or random copolymers selected from polyethylene glycol, polypropylene glycol, and polytetramethylene glycol; random copolymers or block copolymers of ethylene oxide and propylene oxide, or ethylene oxide and butylene oxide; polyglycerin, polyethylene oxide-polyvinyl alcohol graft copolymer; etc. Among them, the water-soluble polymer C is more preferably at least one of polypropylene glycol and polytetramethylene ether glycol, and more preferably polypropylene glycol.
[0076] The weight average molecular weight of the water-soluble polymer C is not particularly limited, but is preferably 100 or more, preferably 200 or more, and more preferably 300 or more. The weight average molecular weight of the water-soluble polymer C is not particularly limited, but is preferably 10,000 or less, more preferably 5,000 or less, and even more preferably 1,000 or less. That is, the weight average molecular weight of the water-soluble polymer C is preferably 100 or more and 10,000 or less, preferably 200 or more and 5,000 or less, and even more preferably 300 or more and 1,000 or less.
[0077] The water-soluble polymer C may be used alone or in combination of two or more. In addition, the water-soluble polymer C may be a commercially available product or a synthetic product.
[0078] The lower limit of the concentration (content) of the water-soluble polymer C in the polishing composition is preferably 0.05% by mass or more, more preferably 0.1% by mass or more, even more preferably 0.15% by mass or more, and particularly preferably 0.2% by mass or more. The upper limit of the concentration (content) of the water-soluble polymer C in the polishing composition is preferably 5% by mass or less, more preferably 3% by mass or less, even more preferably 1% by mass or less, and particularly preferably less than 1% by mass. That is, the concentration (content) of the water-soluble polymer C in the polishing composition is preferably 0.05% by mass or more and 5% by mass or less, more preferably 0.1% by mass or more and 3% by mass or less, even more preferably 0.15% by mass or more and 1% by mass or less, and particularly preferably 0.2% by mass or more and less than 1% by mass.
[0079] When the polishing composition contains two or more kinds of water-soluble polymers C, the concentration (content) of the water-soluble polymers C means the total amount thereof.
[0080] [pH and pH adjusters] The pH of the polishing composition according to the present invention is less than 7.0. When the pH is 7.0 or more, the zeta potential of the silicon nitride to be polished becomes negative, so that electrostatic repulsion with the abrasive grains having a negative zeta potential occurs, and the polishing rate decreases. The pH is preferably 6.0 or less, more preferably 5.5 or less, even more preferably 5.0 or less, and particularly preferably 4.5 or less. The pH is also preferably 1.0 or more, more preferably 1.5 or more, and even more preferably 2.0 or more. That is, the pH of the polishing composition according to the present invention is preferably 1.0 or more and 6.0 or less, more preferably 1.5 or more and 5.5 or less, even more preferably 2.0 or more and 5.0 or less, and particularly preferably 2.0 or more and 4.5 or less.
[0081] The polishing composition of the present invention may contain a pH adjuster for adjusting pH. The pH adjuster may be either an acid or a base, and may be either an inorganic compound or an organic compound. The pH adjuster may be used alone or in combination of two or more kinds.
[0082] Specific examples of acids that can be used as a pH adjuster include inorganic acids such as hydrochloric acid, sulfuric acid, nitric acid, hydrofluoric acid, boric acid, carbonic acid, hypophosphorous acid, phosphorous acid, and phosphoric acid; and organic acids such as formic acid, acetic acid, propionic acid, butyric acid, valeric acid, 2-methylbutyric acid, n-hexanoic acid, 3,3-dimethylbutyric acid, 2-ethylbutyric acid, 4-methylpentanoic acid, n-heptanoic acid, 2-methylhexanoic acid, n-octanoic acid, 2-ethylhexanoic acid, benzoic acid, glycolic acid, salicylic acid, glyceric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, maleic acid, phthalic acid, malic acid, tartaric acid, citric acid, lactic acid, diglycolic acid, 2-furancarboxylic acid, 2,5-furandicarboxylic acid, 3-furancarboxylic acid, 2-tetrahydrofurancarboxylic acid, methoxyacetic acid, methoxyphenylacetic acid, and phenoxyacetic acid.
[0083] Examples of bases that can be used as pH adjusters include amines such as aliphatic amines and aromatic amines, organic bases such as quaternary ammonium hydroxide, alkali metal hydroxides such as sodium hydroxide and potassium hydroxide, hydroxides of alkaline earth metals (group 2 elements), and ammonia.
[0084] The amount of pH adjuster to be added is not particularly limited, and can be appropriately adjusted so that the polishing composition has a desired pH. The pH of the polishing composition can be measured, for example, by a pH meter, and specifically, can be measured by the method described in Examples.
[0085] [Dispersion medium] The polishing composition according to the present invention preferably further contains a dispersion medium. Examples of the dispersion medium include water; alcohols such as methanol, ethanol, and ethylene glycol; ketones such as acetone, and mixtures thereof. Of these, water is preferable as the dispersion medium. That is, according to a more preferred embodiment of the present invention, the dispersion medium contains water. According to a more preferred embodiment of the present invention, the dispersion medium is substantially composed of water. Note that the above "substantially" means that a dispersion medium other than water may be included as long as the objective effect of the present invention can be achieved, and more specifically, the dispersion medium is preferably composed of 90% by mass or more and 100% by mass or less of water and 0% by mass or more and 10% by mass or less of a dispersion medium other than water, and more preferably composed of 99% by mass or more and 100% by mass or less of water and 0% by mass or more and 1% by mass or less of a dispersion medium other than water. Most preferably, the dispersion medium is water.
[0086] From the viewpoint of not inhibiting the action of the components contained in the polishing composition, it is preferable for the dispersion medium to be water that contains as few impurities as possible. Specifically, pure water or ultrapure water from which impurity ions have been removed with an ion exchange resin and then foreign matter has been removed through a filter, or distilled water is more preferable.
[0087] [Electrical Conductivity of Polishing Composition] The electrical conductivity (EC) of the polishing composition according to the present invention is not particularly limited, but is preferably 1 mS / cm or more, more preferably 3 mS / cm or more. The electrical conductivity (EC) of the polishing composition according to the present invention is preferably 20 mS / cm or less, more preferably 15 mS / cm or less. That is, the electrical conductivity (EC) of the polishing composition according to the present invention is preferably 1 mS / cm or more and 20 mS / cm or less, more preferably 3 mS / cm or more and 15 mS / cm or less. If the electrical conductivity (EC) of the polishing composition is in such a range, the polishing rate of silicon nitride can be maintained high. In addition, the repulsion between colloidal silica particles can be appropriately adjusted to ensure stability. The electrical conductivity of the polishing composition can be adjusted by the type and amount of inorganic salt, pH adjuster, etc. The electrical conductivity (EC) of the polishing composition can be measured by the method described in the Examples.
[0088] [Other ingredients] The polishing composition of the present invention may further contain other components such as complexing agent, metal corrosion inhibitor, preservative, antifungal agent, reducing agent, surfactant, etc. Hereinafter, the preservative and antifungal agent, which are preferred components, will be described. Also, the oxidizing agent will be described.
[0089] (Preservatives and fungicides) Examples of preservatives and antifungal agents that can be added to the polishing composition of the present invention include isothiazoline preservatives such as 2-methyl-4-isothiazolin-3-one and 5-chloro-2-methyl-4-isothiazolin-3-one, paraoxybenzoic acid esters, and phenoxyethanol, etc. These preservatives and antifungal agents may be used alone or in combination of two or more.
[0090] (Oxidizing agent) The polishing composition according to the present invention preferably does not substantially contain an oxidizing agent. If an oxidizing agent is contained in the polishing composition, the surface of the object to be polished may be oxidized to generate an oxide film, which may result in a longer polishing time. Specific examples of the oxidizing agent include hydrogen peroxide (H2O2), sodium persulfate, ammonium persulfate, and sodium dichloroisocyanurate. The polishing composition being substantially free of an oxidizing agent means that the oxidizing agent is not intentionally contained at least. Therefore, a polishing composition that inevitably contains a small amount of an oxidizing agent due to raw materials, manufacturing method, etc. is included in the concept of a polishing composition that does not substantially contain an oxidizing agent. For example, the concentration (content) of the oxidizing agent relative to the total mass of the polishing composition is preferably less than 0.01 mass% (100 mass ppm), more preferably 0.005 mass% (50 mass ppm) or less. The lower limit of the concentration (content) of the oxidizing agent is preferably 0 mass% or more, more preferably 0.0005 mass% (5 mass ppm) or more.
[0091] [Form of polishing composition] The polishing composition according to the present invention is typically supplied to an object to be polished in the form of a polishing liquid containing the polishing composition, and is used to polish the object to be polished. The polishing composition according to the present invention may be used as a polishing liquid after dilution (typically diluted with water), or may be used as a polishing liquid as it is. That is, the concept of the polishing composition according to the present invention includes both a polishing composition (working slurry) that is supplied to an object to be polished and used to polish the object to be polished, and a concentrated liquid (original working slurry liquid) that is diluted and used for polishing. The concentration ratio of the concentrated liquid can be, for example, about 2 to 100 times on a volume basis, and is usually about 3 to 50 times.
[0092] [Polished object] The object to be polished according to the present invention is not particularly limited, and examples thereof include single crystal silicon, polycrystalline silicon (polysilicon), polycrystalline silicon doped with n-type or p-type impurities, amorphous silicon, amorphous silicon doped with n-type or p-type impurities, silicon oxide, silicon nitride, silicon carbonitride (SiCN), metals, SiGe, carbon-containing materials, and the like.
[0093] Examples of objects to be polished that contain silicon oxide include a TEOS-type silicon oxide film (hereinafter simply referred to as "TEOS" or "TEOS film") produced using tetraethyl orthosilicate as a precursor, a high density plasma (HDP) film, an undoped silicate glass (USG) film, a phosphorus silicate glass (PSG) film, a boron-phosphorus silicate glass (BPSG) film, and a rapid thermal oxidation (RTO) film.
[0094] Examples of metals include tungsten, copper, aluminum, cobalt, hafnium, nickel, gold, silver, platinum, palladium, rhodium, ruthenium, iridium, and osmium.
[0095] Examples of carbon-containing materials include amorphous carbon, spin-on carbon (SOC), diamond-like carbon (DLC), nanocrystalline diamond, graphene, low-k materials such as SiOC (carbon-containing silicon oxide in which SiO2 is doped with C), silicon carbide, etc. Films containing carbon-containing materials can be formed by CVD, PVD, spin coating, etc.
[0096] The object to be polished may be a commercially available product or may be produced by a known method.
[0097] Among these, an object to be polished containing silicon nitride is preferable. Therefore, according to a preferred embodiment of the present invention, the polishing composition is used for polishing an object to be polished containing silicon nitride.
[0098] [Method of manufacturing the polishing composition] The method for producing the polishing composition according to the present embodiment is not particularly limited, and can be obtained, for example, by stirring and mixing abrasive grains, water-soluble polymer A, and other additives that are added as necessary. The details of each component are as described above.
[0099] The temperature at which the components are mixed is not particularly limited, but is preferably 10° C. to 40° C. Heating may be performed to increase the dissolution rate. The mixing time is also not particularly limited as long as the components can be mixed uniformly.
[0100] [Polishing method and semiconductor substrate manufacturing method] As described above, the polishing composition according to this embodiment is particularly suitable for use in polishing an object having silicon nitride. Thus, the present invention provides a polishing method for polishing an object containing silicon nitride with the polishing composition according to this embodiment. The present invention also provides a method for producing a semiconductor substrate, comprising polishing a semiconductor substrate containing silicon nitride by the above-mentioned polishing method.
[0101] As a polishing device, a general polishing device can be used that is equipped with a holder for holding a substrate or the like having an object to be polished, a motor whose rotation speed can be changed, and a polishing platen onto which a polishing pad (polishing cloth) can be attached.
[0102] The polishing pad may be made of any material, including general nonwoven fabric, polyurethane, porous fluororesin, etc. It is preferable that the polishing pad has grooves formed thereon to allow the polishing liquid to accumulate.
[0103] Regarding the polishing conditions, for example, the rotation speed of the polishing table (platen) and carrier (head) was 10 rpm (0.17 s -1 ) or more 500rpm (8.33s-1 The pressure (polishing pressure) applied to the substrate having the object to be polished is preferably 0.5 psi (3.45 kPa) or more and 10 psi (68.9 kPa) or less.
[0104] The method of supplying the polishing composition to the polishing pad is not particularly limited, and for example, a method of continuously supplying the composition using a pump, etc. is adopted. There is no limit to the amount of the composition supplied, but it is preferable that the surface of the polishing pad is always covered with the polishing composition according to the present invention.
[0105] The polishing composition according to the present embodiment may be a one-liquid type or a multi-liquid type such as a two-liquid type. The polishing composition according to the present invention may be prepared by diluting the stock solution of the polishing composition with a diluting solution such as water, for example, 2 to 100 times, usually 3 to 50 times, on a volume basis.
[0106] [Polishing speed] As described above, the polishing composition of the present invention has a high removal rate for silicon nitride.
[0107] In the present invention, the polishing speed for silicon nitride is preferably 100 Å / min or more, more preferably 150 Å / min or more, and even more preferably 190 Å / min or more.
[0108] [Number of residues] As described above, the polishing composition of the present invention can reduce the number of residues on the surface of silicon nitride. The number of residues is preferably 1000 or less, more preferably 500 or less, and even more preferably 250 or less (lower limit: 0).
[0109] Although the embodiments of the present invention have been described in detail, it is apparent that the same are illustrative and exemplary, not restrictive, and the scope of the present invention should be interpreted by the appended claims.
[0110] The present invention encompasses the following aspects and configurations. 1. A polishing composition comprising an abrasive grain and a water-soluble polymer containing a structural unit derived from an acrylic acid ester, the pH being less than 7.0, and the zeta potential of the abrasive grain in the polishing composition being negative: 2. The polishing composition according to 1 above, wherein the acrylic ester is at least one selected from the group consisting of methyl acrylate, ethyl acrylate, butyl acrylate, and 2-ethylhexyl acrylate. 3. The polishing composition according to 1. or 2. above, wherein the water-soluble polymer further contains a constituent unit derived from another monomer copolymerizable with the acrylic acid ester: 4. The polishing composition according to 3 above, wherein the other monomer copolymerizable with the acrylic ester is an unsaturated carboxylic acid or a salt thereof. 5. The polishing composition according to 3. or 4. above, wherein the other monomer copolymerizable with the acrylic ester is ammonium acrylate. 6. The polishing composition according to any one of 1. to 5. above, wherein the abrasive grains are anion-modified colloidal silica. 7. The polishing composition according to any one of 1. to 6. above, further comprising an inorganic salt: 8. The polishing composition according to any one of 1. to 7. above, further comprising a dispersion medium: 9. The polishing composition according to any one of 1. to 8. above, which is substantially free of an oxidizing agent: 10. The polishing composition according to any one of 1. to 9. above, which is used for polishing an object to be polished containing silicon nitride: 11. A polishing method comprising a step of polishing an object containing silicon nitride with the polishing composition according to any one of 1. to 10. above: 12. A method for producing a semiconductor substrate, comprising the step of polishing a semiconductor substrate containing silicon nitride by the polishing method described in 11 above. EXAMPLES
[0111] The present invention will be described in more detail using the following examples and comparative examples. However, the technical scope of the present invention is not limited to the following examples. Unless otherwise specified, "%" and "parts" mean "% by mass" and "parts by mass", respectively. In the following examples, unless otherwise specified, the operations were performed under the conditions of room temperature (20°C to 25°C) / relative humidity 40% RH to 50% RH. Each physical property was measured as follows.
[0112] <Average secondary particle size of abrasive grains> The average secondary particle diameter of the abrasive grains was measured as the volume average particle diameter (arithmetic mean diameter based on volume; Mv) using a dynamic light scattering particle size / particle size distribution analyzer UPA-UTI151 (manufactured by Nikkiso Co., Ltd.).
[0113] <Zeta potential of abrasive grains> The zeta potential of the abrasive grains was measured by the laser Doppler method (electrophoretic light scattering measurement method) using a flow cell at a measurement temperature of 25° C., by feeding the polishing composition prepared below to ELS-Z2 manufactured by Otsuka Electronics Co., Ltd. The obtained data was analyzed by the Smoluchowski formula to calculate the zeta potential of the abrasive grains contained in the polishing composition.
[0114] <pH of polishing composition> The pH of the polishing composition was measured with a pH meter (manufactured by Horiba, Ltd., model number: LAQUA).
[0115] <Weight average molecular weight of water-soluble polymer> The weight average molecular weight of the water-soluble polymer was measured by gel permeation chromatography (GPC) under the following measurement conditions.
[0116] (GPC measurement conditions) Measuring device: HLC-8320GPC (Tosoh Corporation) Sample concentration: 0.01% by mass Column: TSKgel GMPWXL Detector: Differential refractometer Eluent: 10 mM lithium bromide dissolved in N,N-dimethylformamide Flow rate: 1mL / min Measurement temperature: 40℃ Molecular weight conversion: Polyethylene glycol conversion Sample injection volume: 200 μL.
[0117] <Electrical Conductivity of Polishing Composition> The electrical conductivity (EC) of the polishing composition was measured with a tabletop electrical conductivity meter (manufactured by Horiba, Ltd., model number: DS-71 LAQUA (registered trademark)).
[0118] <Sulfonic acid immobilized colloidal silica> The sulfonic acid-fixed colloidal silica (anion-modified colloidal silica) contained in the polishing composition was prepared by using colloidal silica having an average primary particle size of 35 nm, an average secondary particle size of 70 nm, and an average degree of association of 2, according to the method described in “Sulfonic acid-functionalized silica through quantitative oxidation of thiol groups”, Chem. Commun. 246-247 (2003).
[0119] Example 1 <Preparation of Polishing Composition> To water as a dispersion medium, sulfonic acid-fixed colloidal silica (average secondary particle size: 70 nm, cocoon-shaped) serving as abrasive grains was added so that the final concentration was 2.3 mass %. Further, polyvinyl alcohol (PVA, weight average molecular weight (Mw): 10,000, manufactured by Nippon Vinyl Acetate & Poval Co., Ltd., product name: JMR-10HH) was added to a final concentration of 0.075 mass%, polypropylene glycol (PPG, weight average molecular weight (Mw): 400, manufactured by Sanyo Chemical Industries, Ltd.) was added to a final concentration of 0.6 mass%, methyl acrylate-ammonium acrylate copolymer (weight average molecular weight (Mw): 8,000, manufactured by Toagosei Co., Ltd., product name: Aron (registered trademark) A-6114) was added to a final concentration of 0.02 mass% (200 mass ppm), and ammonium sulfate (manufactured by Toyama Pharmaceutical Co., Ltd.) as an inorganic salt was added to a final concentration of 0.504 mass%, and the mixture was stirred and mixed (stirring temperature: 25°C, stirring time: 20 minutes). The pH of the polishing composition was adjusted to pH 2.1 using nitric acid to complete polishing composition 1. The resulting Polishing Composition 1 had an electrical conductivity of 12.04 mS / cm, and the abrasive grains in the Polishing Composition 1 had a zeta potential of -19.29 mV.
[0120] Example 2 Polishing composition 2 was prepared in the same manner as in Example 1, except that the methyl acrylate-ammonium acrylate copolymer was added so that the final concentration in the composition was 0.05 mass% (500 mass ppm). The electrical conductivity of the obtained polishing composition 2 was 12.05 mS / cm, and the zeta potential of the abrasive grains in polishing composition 2 was -18.99 mV.
[0121] Comparative Example 1 Polishing Composition Comparison 1 was prepared in the same manner as in Example 1, except that sodium polystyrene sulfonate (weight average molecular weight (Mw): 20,000, manufactured by Tosoh Finechem Corporation, product name: Polynas (registered trademark) PS-1) was added in place of the methyl acrylate-ammonium acrylate copolymer so that the final concentration in the composition was 0.001 mass % (10 mass ppm). The electrical conductivity of the obtained Polishing Composition Comparison 1 was 12.02 mS / cm, and the zeta potential of the abrasive grains in Polishing Composition Comparison 1 was -19.4 mV.
[0122] Comparative Example 2 Comparative polishing composition 2 was prepared in the same manner as in Comparative Example 1, except that sodium polystyrene sulfonate was added so that the final concentration in the composition was 0.002 mass% (20 mass ppm). The electrical conductivity of the obtained polishing composition 2 was 12.02 mS / cm, and the zeta potential of the abrasive grains in polishing composition 2 was -19.4 mV.
[0123] Comparative Example 3 Polishing composition comparison 3 was prepared in the same manner as in Example 1, except that sodium polyacrylate (weight average molecular weight (Mw): 6,000, manufactured by Toagosei Co., Ltd., product name: Aron (registered trademark) T-50) was added to a final concentration of 0.05 mass% (500 mass ppm) instead of the methyl acrylate-ammonium acrylate copolymer. The electrical conductivity of the obtained polishing composition comparison 3 was 12.04 mS / cm, and the zeta potential of the abrasive grains in polishing composition comparison 3 was -18.09 mV.
[0124] Comparative Example 4 Except for not adding ammonium sulfate, Comparative Polishing Composition 4 was prepared in the same manner as in Comparative Example 1. The electrical conductivity of the obtained Comparative Polishing Composition 4 was 1.795 mS / cm, and the zeta potential of the abrasive grains in Comparative Polishing Composition 4 was -43.3 mV.
[0125] The compositions of the polishing compositions of Examples and Comparative Examples are shown in the following Table 1. In addition, "-" in the following Table 1 means that the component is not contained.
[0126] [Table 1]
[0127] [evaluation] The object to be polished was a silicon wafer (300 mm, blanket wafer) with a 1000 Å thick silicon nitride (Si3N4) film formed on its surface. The wafer was polished under the following conditions: <Polishing conditions> Polishing machine: 300mm polishing machine (manufactured by Ebara Corporation, model number: F-REX300E) Polishing pad: Polyurethane pad (Nitta DuPont, IC1000) Pressure: 2.0 psi (13.79 kPa) Polishing platen rotation speed: 30 rpm Carrier (head) rotation speed: 31 rpm Flow rate of polishing composition: 200ml / min Polishing time: 60 seconds.
[0128] <Polishing speed> The polishing speed (polishing rate) of the object to be polished was calculated by the following formula.
[0129]
number
[0130] The film thickness of the object to be polished before and after polishing was measured using an optical interference film thickness measuring device (KLA-Tencor Corporation, model number: A-SET F5X), and the polishing rate was calculated by dividing the difference by the polishing time.
[0131] <Number of residues> Using a Surfscan (registered trademark) SP-5 manufactured by KLA-Tencor Corporation, the total number of residues with a size of 0.07 μm or more remaining on the surface of a polished object having a silicon nitride film was measured.
[0132] The evaluation results of the polishing rate and the number of residues are shown in Table 2 below.
[0133] [Table 2]
[0134] As is clear from Table 2 above, when the polishing composition of the embodiment is used, the polishing rate of silicon nitride is high and the residue on the surface of the polished object (silicon nitride) is small. On the other hand, when the polishing composition of the comparative example is used, at least one of the polishing rate and the number of residues is deteriorated.
Claims
1. Abrasive grains and A water-soluble polymer including a structural unit derived from an acrylic acid ester; and having a pH of less than 7.0; A polishing composition, wherein the abrasive grains in the polishing composition have a negative zeta potential.
2. 2. The polishing composition according to claim 1, wherein the acrylic ester is at least one selected from the group consisting of methyl acrylate, ethyl acrylate, n-butyl acrylate, and 2-ethylhexyl acrylate.
3. The polishing composition according to claim 1 , wherein the water-soluble polymer further contains a structural unit derived from another monomer copolymerizable with the acrylic acid ester.
4. The polishing composition according to claim 3 , wherein the other monomer copolymerizable with the acrylic ester is an unsaturated carboxylic acid or a salt thereof.
5. 5. The polishing composition according to claim 4, wherein the other monomer copolymerizable with the acrylic ester is ammonium acrylate.
6. The polishing composition according to claim 1 , wherein the abrasive grains are anion-modified colloidal silica.
7. The polishing composition of claim 1 , further comprising an inorganic salt.
8. The polishing composition according to claim 1 , further comprising a dispersion medium.
9. The polishing composition according to claim 1 , which is substantially free of an oxidizing agent.
10. The polishing composition according to claim 1 , which is used in polishing an object containing silicon nitride.
11. 11. A polishing method comprising a step of polishing an object containing silicon nitride with the polishing composition according to claim 1.
12. A method for producing a semiconductor substrate, comprising the step of polishing a semiconductor substrate containing silicon nitride by the polishing method according to claim 11.
Citation Information
Patent Citations
Polishing composition and polishing method using the same
JP2012040671A